2017
DOI: 10.2334/josnusd.16-0651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochanin A versus 17β estradiol in rat submandibular salivary gland

Abstract: Abstract:The epigenetic nature of development mandates the observation of the effect of any exogenous substance, especially those with estrogenic activities, during critical phases of development. The submandibular gland (SMG) presents as a great model due to extensive postnatal development, and is known to be regulated and affected by hormones as well as growth factors. Herein, we observed postnatal development following low doses of Biochanin A (BCA) and 17β estradiol (E2) in rats. The pups were randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Because ERβ activation was also related with the induction of apoptosis in PC-3M cells, apoptotic cell death may result not only from cytotoxic activity of extract components, but also could be used as functional link for agonistic aglycons binding to ERβ protein [53]. On the other hand, studies performed on the submandibular gland of the rat (an extensive postnatal development model) revealed that by biochanin A was involved in ERβ expression up-regulation [54]. Since estrogenicity is connected with cell proliferation, we evaluated indirectly estrogenic-like effects of T. pratense phenolics at dosages lower than IC 0 through the measurement of MCF-7 cells with crystal violet staining.…”
Section: The Influene Of Trifolium Pratense L On Gene Expressionmentioning
confidence: 99%
“…Because ERβ activation was also related with the induction of apoptosis in PC-3M cells, apoptotic cell death may result not only from cytotoxic activity of extract components, but also could be used as functional link for agonistic aglycons binding to ERβ protein [53]. On the other hand, studies performed on the submandibular gland of the rat (an extensive postnatal development model) revealed that by biochanin A was involved in ERβ expression up-regulation [54]. Since estrogenicity is connected with cell proliferation, we evaluated indirectly estrogenic-like effects of T. pratense phenolics at dosages lower than IC 0 through the measurement of MCF-7 cells with crystal violet staining.…”
Section: The Influene Of Trifolium Pratense L On Gene Expressionmentioning
confidence: 99%
“…BCA may act as a natural selective ER modulator that elicits distinct clinical effects from estrogens used for hormone replacement by selectively recruiting coregulatory proteins to ERβ to trigger transcriptional pathways. As a promising alternative estrogen therapy, BCA might be used for the management of the renal and cutaneous changes observed in postmenopausal women while preventing bone loss (An et al, 2001; Beck et al, 2003; Hellström and Muntzing, 2012; Elsherbini et al, 2017; Galal et al, 2018). BCA is well known for its regulation of blood glucose and has significant effects in type 2 diabetes mellitus in vivo by affecting mechanisms that influence autophagy, differentiation, inflammation, and metabolism (Mehrabadi et al, 2018; Nikolic et al, 2018; Oza and Kulkarni, 2018).…”
Section: Bca May Play a Therapeutic Role In Metabolic Disordersmentioning
confidence: 99%